2018
DOI: 10.1088/1361-6463/aaae79
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PECVD ultralow dielectric constant porous SiOCH films using triethoxymethylsilane precursor and cinene porogen

Abstract: Ultralow dielectric-constant (k) SiOCH films were prepared from triethoxymethylsilane (MTES) and cinene (LIMO) by plasma-enhanced chemical vapor deposition (PECVD). By changing the mass flow rate ratio (MFRR) of LIMO/MTES, the properties of the low k films were investigated. In particular, the chemical composition and bonding structure of the deposited film were analyzed with the help of Fourier transforms infrared spectroscopy and x-ray photoelectron spectroscopy. It was revealed that the bonding configuratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…The assumption that the density is the same for all of the coatings is not necessarily a good assumption. Previous studies have shown that the porosity and density change with deposition conditions . Characterization of the rate of deposition by mass per area would be preferred.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The assumption that the density is the same for all of the coatings is not necessarily a good assumption. Previous studies have shown that the porosity and density change with deposition conditions . Characterization of the rate of deposition by mass per area would be preferred.…”
Section: Resultsmentioning
confidence: 99%
“…FTIR spectra were obtained for films of various levels of W / FM and the absorbance values are shown in Figure for HMDSO and Figure for D5. The peaks assignments are summarized in Table and are based on published spectra for organosilicon materials and plasma‐deposited thin films . The absorbance spectra show the presence of Si–CH 3 groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results strongly indicate that the borazine-aBN films also offer superior Young's modulus (> 50 GPa), particularly at the region of k values<3, compared to other Si-and BC-based low-k materials. [8,11,12,[31][32][33][38][39][40] Recent atomistic simulation results also have shown that the Young's modulus increase with increasing the initial density of aBN microstructure is due to 80% sp 2 hybridization and 60% of atoms in hexagonal ring. [41] Therefore, we ascribe the superior mechanical strength of borazine-aBN films to the high density that originates from the matching stacking B-N hexagonal ring stucture.…”
Section: Thermal Stabilities and Mechanical Propertiesmentioning
confidence: 99%